2021
DOI: 10.1017/s1463423621000578
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of health-related knowledge, attitudes, and behaviors of undergraduate students by cardiovascular risk factors

Abstract: Aim: To determine the presence of cardiovascular (CV) risk (CVR) factors in university students and evaluate how these factors are affected from the knowledge, attitudes, and habits of the individuals regarding healthy lifestyle. Background: Starting from early ages, lifestyle habits such as lack of physical activity, unhealthy eating, and inappropriate drug use increase CV and metabolic risks of individuals. Methods: In April–May 2018, sociodemographic characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…Furthermore, in accordance with the previous study [17], no significant differences emerged between IT and SP concerning the adherence to MD. It has been reported that the most common cardiovascular risk factors in undergraduate students with a low adherence to MD (11.3% reported a good compliance with MD) were smoking (20.6%), high TC (7.5%), and high BP (6.0%) [48]. In our sample, the prevalence of smoking was lower and the other CVD risk factors were related to fruit and vegetable consumption.…”
Section: Discussionmentioning
confidence: 49%
“…Furthermore, in accordance with the previous study [17], no significant differences emerged between IT and SP concerning the adherence to MD. It has been reported that the most common cardiovascular risk factors in undergraduate students with a low adherence to MD (11.3% reported a good compliance with MD) were smoking (20.6%), high TC (7.5%), and high BP (6.0%) [48]. In our sample, the prevalence of smoking was lower and the other CVD risk factors were related to fruit and vegetable consumption.…”
Section: Discussionmentioning
confidence: 49%